Design and description of a classification system framework for easier reuse - Lopes, Sérgio F. (2007)
Frameworks are an important technology to reduce software development costs and shorten the time-to-market. However, framework complexity presents re-use problems that limit its success as an application development alternative. It has been widely recognized that is necessary to effectively communicate frameworks and provide appropriate tool support, but we argue that difficulties are also related to the considered framework model. We find that the level of support that tools can provide is decisively dependent on the kind of available framework documentation, which in turn is intimately tied to the considered framework model. In this paper, we present our framework model and respective supporting notation. We describe their appliance to the design and description of an application framework. This case study illustrates how the proposed model and documentation approach alleviate difficulties of framework reuse, namely its comprehension and instantiation.